Facing the 2020 pandemic: What does cyberbiosecurity want us to know to safeguard the future? - Siguna Mueller (Elsevier, 2021)
As the entire world is under the grip of the coronavirus disease 2019 (COVID-19), and as many are eagerly trying to explain the origins of the virus and cause of the pandemic, it is imperative to place more attention on related potential biosafety risks. Biology and biotechnology have changed dramatically during the last ten years or so. Their reliance on digitization, automation, and their cyber-overlaps have created new vulnerabilities for unintended consequences and potentials for intended exploitation that are mostly under-appreciated. This study summarizes and elaborates on these new cyberbiosecurity challenges, (1) in terms of comprehending the evolving threat landscape and determining new risk potentials, (2) in developing adequate safeguarding measures, their validation and implementation, and (3) specific critical risks and consequences, many of them unique to the life-sciences. Drawing other's expertise and my previous work, this article reviews and critically interprets our current bio-economy situation. The goal is not to attribute causative aspects of past biosafety or biosecurity events, but to highlight the fact that the bioeconomy harbors unique features that have to be more critically assessed for their potential to unintentionally cause harm to human health or environment, or to be re-tasked with an intention to cause harm. It is concluded with recommendations that will need to be considered to help ensure converging and emerging biorisk challenges, in order to minimize vulnerabilities to the life-science enterprise, public health, and national security.